Determinants of Household Food Insecurity and Depression in Mothers: Evidence from Ghana - Anthony Wemakor; Ibrahim Alhassan Mohammed; Victoria Awuni (Hindawi Limited, 2023)
Background. Household food insecurity (FI) and maternal depression are serious public health problems, especially in low-income countries. The aims of this study were to determine the determinants of household FI and depression in mothers and the association between these constructs in Savelugu Municipality, Ghana. Methods. An analytical, community-based, cross-sectional survey was conducted to collect data on 364 mothers of under-five children selected using the multistage method in the municipal. Household FI and maternal depression were measured using the FI Experience Scale and Patient Health Questionnaire 9-item in personal interviews. Logistic regression analysis was used to identify the factors associated with household FI and maternal depression and the association between these two constructs. Results. The mean age of mothers was 30.1(±6.5) years with almost all practising Islamic religion (96.2%) and were married (96.7%). The prevalence of household FI and maternal depression were 51.6% and 25.3%, respectively. The determinants of household FI were mother's self-health rating, social support, nutrition knowledge, and household's source of drinking water, while those of maternal depression were the mother's work, place of residence, self-health rating, and nutrition knowledge. In multivariable adjusted logistic regression analysis, women in food insecure households were about three times more likely than women in food secure households to be depressed (adjusted odds ratio = 2.49; 95% confidence interval: 1.36-4.55; and p=0.003). Conclusion. The current study shows a high prevalence of both household FI and depression in mothers in Savelugu Municipality. Both personal and household characteristics of the women are associated with household FI and maternal depression statuses, and the two constructs are highly correlated. It is recommended to include depression assessment in interventions for FI.